African American English intensifier dennamug: Using twitter to investigate syntactic change in low-frequency forms - Jones, Taylor (Frontiers in Artificial Intelligence, 2023)
There are some linguistic forms that may be known to both speakers and linguists, but that occur naturally with such low frequency that traditional sociolinguistic methods do not allow for study. This study investigates one such phenomenon: the grammatical reanalysis of an intensifier in some forms of African American English—from a full phrase [than a mother(fucker)] to lexical word (represented here as dennamug)—using data gathered from twitter. This paper investigates the relationship between apparent lexicalization and deletion of the comparative morpheme on the preceding adjective. While state-of-the-art traditional corpora contain so few tokens they can be counted on one hand, twitter yields almost 300,000 tokens over a 10 year sample period. This paper uses web scraping of Twitter to gather all plausible orthographic representations of the intensifier, and uses logistic regression to analyze the extent to which markers of lexicalization and reanalysis are associated with a corresponding shift from comparative to bare morphology on the adjective the intensifier modifies, finding that, indeed, degree of apparent lexicalization is strongly associated with bare morphology, suggesting ongoing lexicalization and subsequent reanalysis at the phrase level. This digital approach reveals ongoing grammatical change, with the new intensifier associated with bare, note comparative, adjectives, and that there is seemingly stable variation correlated with the degree to which the intensifier has lexicalized. Orthographic representations of African American English on social media are shown to be a locus of identity construction and grammatical change.